تحولات الخط العربي في العصر الرقمي: نماذج تعليمية وتطويرية: Transformasi Khat Arab Era Digital: Analisis Model Pendidikan dan Pengembangan - Hasbullah, Abdur Rouf; Makhisoh, Iis (Jiluna Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2025)
A variety of technological tools, digital media, and social media have streamlined learning, particularly for Tahsin al-Kitabah (improving writing) and Khat Araby (Arabic calligraphy). Online correction systems and diverse calligraphy applications like Kitabahku, Mashq, Ana Mukhtarifulkhat, and Kelk not only aid student learning but also stimulate their creativity. Consequently, educators must leverage these digital media as supportive learning tools. The "Abajadun" method for Tahsin al-Kitabah and Manhaj Hamidi for Khat Araby each offer distinct advantages. The Abajadun method emphasizes understanding writing "keys" through the letters alif, ba', jim, and dal, while Manhaj Hamidi employs a tiered system, progressing from simpler to more complex calligraphy styles, with the added benefit of a Khat Diploma to standardize the Sanad system. Both innovative methods primarily utilize digital media to support the learning process. The results indicate an increase in the effectiveness of calligraphy learning. Although some practical challenges exist, continuous efforts to improve and enhance learning quality are essential. The use of applications like Kitabahku and digital guidebooks represents a Learning Visualization model, as students are significantly aided in comprehending Tahsin al-Kitabah and Khat Araby writing. Furthermore, utilizing applications such as Mashq, Ana Mukhtarif al-Khat, and Kelk constitutes a strategy employing the Active Learning model, where students are actively involved in practicing and creating. This enables students to master calligraphy from basic to advanced levels and produce quality work using manual digital media.